Integrating African Traditional Health Knowledge and Practices into Health Sciences Curricula in Higher Education: An Imbizo Approach. Issue 1 (2nd January 2019) - Moeta, Mabitja; Mogale, Ramadimetja Shirley; Mgolozeli, Siyabulela Eric; Moagi, Miriam Mamphamo; Pema-Bhana, Varshika
Abstract: Traditional health knowledge and practices remain the primary source of health services for most African communities. Despite this, the training of health professionals in South African higher education institutions remains underpinned on paradigms based on Western medicine, adversely perpetuating health disparities and widening the gap between health professionals and African health service users. This research describes the views of African traditional knowledge holders, traditional health practitioners, health sciences academics, and nursing students on how African traditional health knowledge and practices can be integrated into health sciences curricula. In this qualitative study, we purposively selected a panel of experts as participants and collected data via a discussion forum. Ideas that stood out from the discussions include the nature of transformation as starting from within, barriers to the co-existence of African and biomedical health systems, and strategies to facilitate integration. This venture has revealed that the successful integration of African traditional health knowledge and practices into existing nursing curricula will require a concerted effort from all stakeholders in order to transform and recognise the value of African traditional medicine. Lessons learnt from adopting an imbizo approach for discussions include improved collaboration and the levelling of power differentials. We recommend that more studies on decolonisation within the African context adopt this methodology to ascertain and strengthen its viability.